Development and characterization of surface solid dispersion of curcumin for solubility enhancement - Singh, Mahendra Vikram; Juyal, Divya; Singh, Vikram; Rawat, Geeta; Tiwari, Akhilesh (Journal of Applied Pharmaceutical Research, 2014)
Surface solid dispersion (SSD) of curcumin was developed and characterized with purview to overcome solubility hurdle in its pharmacokinetic and pharmacodynamic performance. SSDs were prepared by co-evaporation method using polyplasdone XL, croscarmelose sodium, and silicone dioxide and polyethlene glycol 6000 as carrier. The optimized SSD (F9) was characterized using FE-SEM and XRD as an analytical tool. The formulation of modified Curcumin shows better drug release profile as compared to the natural Curcumin. Formulation F9 released more than 90% of the loaded Curcumin within 30 minutes where marketed formulations shows 90% drug only after 60 minutes.